9-(1-3-Dihydroxy-2-propoxymethyl)guanine prevents death but not immunity in murine cytomegalovirus-infected normal and immunosuppressed BALB/c mice. - Wilson, E J (1987)
Immunosuppressed (from treatment with cortisone acetate and anti-thymocyte globulin) and control adult female BALB/c mice, latently infected with murine cytomegalovirus (MCMV) or lethally challenged (10(6) PFU) with MCMV intraperitoneally, were treated with 9-(1-3-dihydroxy-2-propoxymethyl)guanine (DHPG) intraperitoneally. A dose of 3 mg/kg reduced mortality by 50% in lethally challenged normal mice; 10 mg/kg was required in immunosuppressed mice. When 15 mg/kg was given, the onset of treatment could be delayed for 64 h after lethal challenge. DHPG did not prevent the establishment of latent MCMV infection or immunosuppression-induced reactivation. The antibody titer to MCMV in DHPG-treated mice which survived lethal challenge was 41 (reciprocal of geometric mean) 4 to 5 weeks after inoculation; such mice survived a second lethal challenge. When antiserum treatment was begun 64 h and DHPG was begun 72 h after a lethal challenge, most mice survived; most did not when either treatment alone was begun at those times. In summary, DHPG effectively treated lethal MCMV infection even in immunosuppressed mice and even when treatment onset was delayed for 64 h. Treatment did not alter the establishment or reactivation of latent infections or the induction of effective immunity. The administration of DHPG coupled with antiserum treatment may be even more effective than the administration of either alone.